What came as a language in the book to explain Ibn Aqeel on Alfiya Ibn malek (Journal of the College of Education for Women, 2019)
It is found in the book "Ibn Aqeel: Alfiya Ibn Malek" that there are some linqustical aspected are related to the native tribal speakers like Tamim or Tie or some others. Sometimes in the book he said "some Arabian said without mentioning the name of the tribe.As weel, he hasn’t mentioned the accent but he does mention the language. In the book, he has brought back the most important and the biqqest Arabian tribes suchas tribes of Hegaz, Tamim, Hatheyal, son of Anber, Tie, Rabia Bin Wael, Bani Katham, Au there, Bani AL Harth, Bani Kalb, Bani Hgim, Zabid, Hamedan, Alia Qais, Bani Ameer and many others. However, the most mentioned tribes were Hegaz and Tami.Hence, the importance of the book expiain Ibn Aqeel by mentioning these Arabian tribes. As well he has mentioned the importance of some schoolars and linquists such as Al-kafi and Al-Basri. The book has been supported by some examples of poetry, Hadeeth, and some holy veres of the holy Quran